Oil and water? Combining Action Learning with academic theory. (4th May 2021) - Wilkinson, Diane; Mackenzie, Joe
ABSTRACT: This account of practice is about the 'Scale Up' programme, an attempt by an external consultant and their client to implement a model of Action Learning in an academic environment. It tells the story of establishing an Action Learning programme for local business leaders in collaboration with an academic business school. The programme involved classic Action Learning methods and structures, with the addition of external input from expert lecturers. The article explores how the programme was co-created to provide the advantages of both academic expertise and practical tools and highlights the challenges posed by this combination of practice and theory. The central crisis focuses on the first lecturer on the programme, whose behaviour emphasised the divide between academic teaching and practice-based, facilitated learning. By returning to Action Learning concepts, the programme coordinators were able to structure the academic input and ensure the sessions were more in service of the delegates' learning. Reflecting on the programme, the external consultant learned the importance of being clear with collaborators from different learning disciplines, and the unique challenge of combining academia and practice through Action Learning.